Financial Markets And Regulation Of Cashless Implementation - Ayustri Alni, Verina (UMBanjarmasin, 2023)
Digital payment is one of the electronic transactions issued by the government to facilitate public payments during transactions and minimize the circulation of counterfeit money, money theft or robbery. The use of a cashless system is very beneficial for the monetary sector in Indonesia. When the use of cashless transactions increases, it will reduce transaction costs and money exchange will be easier and faster to do, which will have a good impact on Indonesia's output and economic growth. Therefore, if the community is more supportive of the use of a cashless system issued by the government, queuing activities when taking money will be resolved easily and make it easier for us to transact in large quantities.